EFEKTIVITAS PENERAPAN UNDANG-UNDANG NOMOR 24 TAHUN 2011 TENTANG BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN DI RUMAH SAKIT UMUM DAERAH ATAMBUA - Talo, Gramelia Sannyta; Asnawi, Norani; Nuban, Detji Kory Elianor Rooselved (Petitum Law Journal, 2024)
The Social Security Administering Body (BPJS) is a legal entity formed to administer the National Health Insurance Program (JKN). This is a form of the government's commitment to the Implementation of National Social Security in article 5 paragraph (1) that